Familias disfuncionales y calidad de vida en niños con enfermedades respiratorias del Hospital pediátrico “Alfonso Villagómez Román” de Riobamba - Falconí Moreano, Ximena Alexandra (2018)
This investigation was developed in "Alfonso Villagómez Román" Pediatric Hospital of Riobamba. The objective was to analyze the dysfunction family and the quality of life in children with respiratory diseases of the health house. The field of this research is, bibliographic, cross-sectional, non-experimental, quantitative and descriptive research. The study population consisted about 100 children and the sample of 20 children, it is not probabilistic, selected according to inclusion and exclusion criteria. For data collection, the questionnaire "Apgar familiar" was applied to children and parents, with the purpose of identifying dysfunction family at homes, in addition the "Kidscreen-52" questionnaire to establish children's quality of life level. After the application of instruments and tabulation of results, it was concluded that 70% of children manifested moderate family dysfunction in contrast to parents who in 20% expressed the existence of this problem at a moderate level and a 35% of mild dysfunction. By means of the Spearman correlation coefficient, it was determined that the relationship between the variables about dysfunctional family and children’s quality of life with respiratory diseases is of -0.315789474 which is equivalent to mean negative correlation and a very high positive determination of 99 %.